From Policy to Practice: Optimizing IP Management for Innovation in Academic Institutions (Journal of Intellectual Property Rights (JIPR), 2026)
The adoption of the National IPR Policy in 2016 prompted a wave of institutional responses across India's academic landscape, with numerous universities and research institutions drafting their own IP policies. While this proliferation reflects increased awareness and formalization of IP governance, the implementation of these policies often remains superficial, lacking the operational depth required to drive genuine innovation. Concurrently, a growing emphasis on intellectual property metrics—particularly patent filing counts—has led to a focus on quantity over quality, encouraging number-driven reporting at the expense of real-world impact. This paper examines the intersection of these trends through a case study of an Institute of National Importance (INI) in India. It analyzes the institutional mechanisms adopted to translate policy into practice, focusing on the role of the Intellectual Property Management Cell (IPMC). By unpacking the challenges and strategies involved in meaningful IP policy execution, the study highlights the need for a shift from symbolic compliance to substantive outcomes in institutional IP ecosystems.